Development of “Water Detective” Diorama in Islamic Education through Pancasila Student Profile Strengthening Project (P5) - Widiyono, Aan; Nuraini, Latifah; Chasannudin, Arif; Minardi, Joko; Jannah, Aulia Miftahul (Jurnal Tarbiyatuna, 2023)
Having high level human resources that globally competitive is very important in this era of constant changes. The limited use of concrete media contributes to the decline of efficiency, creativity, and involvement in the classes. The purpose of this research is to assess the feasibility and efficiency of various learning media. The ADDIE R&D model is used in this study. The results of the validation test by material and media experts shows a score of 33 out of 40 or 82.5%, which means that this product is "very feasible". The learning expert gives it a score of 38 out of 40 or 95%, which also indicates that the product is "very feasible". The effectiveness test conducted by pretest and posttest shows an increase of 51.6 points, and the questionnaire given to students shows product usability of 90.5%, which means this product is "very feasible". The observation of Pancasila Student Profile Strengthening Project shows that the character of student profile improves from level 2 to level 4. Based on the research result, the “Detective Air” (Water Detective) media can optimally improve learning and can be a reference in facilitating learning process.